Close quarters : contemporary art from Australia and New Zealand. - Barton, Christina; Chapman, Christopher; Laird, Tessa; Stanhope, Zara; Williamson, Clare; Monash University Gallery, Clayton; Australian Centre for Contemporary Art, Clayton; Institute of Modern Art, Brisbane; Canberra School of Art Gallery, Canberra; Govett-Brewster Gallery, New Plymouth; Dunedin Public Art Gallery, Dunedin; Auckland Art Gallery, Auckland (Clayton : Monash University Gallery, 1998)
Bary, Lyell ; L. Budd et al ; Deacon, Destiny ; de Lautour, Tony ; eX de Medici ; Dwyer, Mikala ; Gill, Simryn ; Hansen, Eugene ; Harrison, Michael ; Hastings, Gail ; Kerr, Sean ; Kesminas, Danius ; O'Neill, Ani ; Robertson, Natalie ; Shannon, Marie ; Urbahn, Terry ; Wedge, H.J. ; Zikos, Constanze
biog., bibliog. (selectie) per kunstenaar p. 39-47
Engels
Close quarters : contemporary art from Australia and New Zealand, Monash University Gallery and Australian Centre for Contemporary Art, Clayton, 8 October - 28 November 1998 / Institute of Modern Art, Brisbane, 5 - 27 March 1999 / Canberra School of Art Gallery, Canberra, 2 July - 29 August 1999 / Govett-Brewster Gallery, New Plymouth, 16 September - 6 November 1999 / Dunedin Public Art Gallery, Dunedin, 2000 / Auckland Art Gallery, Auckland, 2000
boek
Keywords: Australië; Nieuw-Zeeland